Smartphone addiction and its impact on quality of sleep and academic performance among nursing students. Institutional based cross-sectional study in Western Rajasthan (India) - Kalal, Nipin; Sabari Vel, N; Angmo, Sonam; Choyal, Sukhi; Bishnoi, Sunaina; Dhaka, Subeeta; Rulaniya, Suman; Banswal, Surbhi (Investigación y Educación en Enfermería, 2023)
Objective. To explore the smartphone addiction and its impact on quality of sleep and academic performance among the nursing students. Methods. A descriptive cross-sectional study was conducted among the nursing students (n=160) in tertiary care teaching hospital in western Rajasthan (India) by using standardized Smartphone Addiction Scale Short Version (SAS-SV), the quality of sleep was assessed by standardized Pittsburg’s Sleep Quality Index scale (PSQI) and academic performance was assessed by self –made Academic Performance Scale. Results. In this study 38.1 % students were having moderate smartphone addiction. The smartphone addiction is directly associated with hours daily spend on smartphone (p < 0.001), time check smartphone after wake up in the morning (p < 0.001), and frequency of smartphone pickups in a day (p=0.003) of students. The quality of sleep is inversely associated with duration of smartphone use (p=0.004), hours daily spend on smartphone (p=0.002), time check smartphone after wake up in morning (p=0.010), of students The academic performance is significantly associated with hours daily spend on smartphone (p=0.003), time check smartphone after wake up in morning (p=0.001), and frequency of smartphone pickups in a day (p=0.015) of students. Conclusion: A high proportion of nursing students have moderate smartphone addiction. This addiction was associated with an increased risk of poor sleep quality and poor academic performance. Educational activities on the healthy use of smartphones are needed in the studied group.